" Obstacles Facing Educational Research at the University: Impeding the Achievement of the Principles of Competitive Advantage and Competitiveness - A Critical Perspective - فهيم .فتوح محمود; سليمان فرج محمد (Tobruk University Journal of Social and Human Sciences, 2024)
The study aimed to identify the obstacles facing scientific educational research at the university that hinder achieving the principle of advantage and competitive ability with a critical vision through the critical and integrative approach, such as deduction at times, induction, and cognitive analysis based on monitoring reality and arguing with it, and rebuilding new relationships to identify shortcomings and treat them with feedback. As a mechanism of the critical philosophical approach, the direct results include the suffering of educational scientific research and its inability to contribute adequately to developing reality and raising the economic and social capabilities of the university, the absence of research plans, team and institutional research, the lack of support, a significant decrease in the percentage of spending, weak paths of innovation and creativity, and a low scientific level. Administrative and financial complexities, the decrease in the average number of researchers, and the significant decrease in the number of patents are an inevitable result of the decline in the university’s research level. Competitiveness is achieved through the best use of the capabilities available for scientific research in terms of material, technical, human and organizational resources, which enable it to design and implement its competitive strategies, while achieving Competitive advantage is based on the perceived value of the university’s beneficiaries, and its ability to achieve excellence, achieve and gain a permanent and continuous comparative advantage in reducing production costs and gain a permanent and continuous comparative advantage in raising and improving the quality of products, offering everything new and stimulating the spirit of innovation and creativity, so competitive ability depends on more than one strategy. For competition as a strategy of excellence, focus, and comprehensive cost leadership as an added value. The competitiveness of scientific research is closely linked to society and the extent to which it meets the needs and requirements of society and depends on the quality of the educational researcher and the extent to which he is equipped with twenty-first century skills.